2008
DOI: 10.1074/jbc.m802089200
|View full text |Cite
|
Sign up to set email alerts
|

Unique Small Molecule Entry Inhibitors of Hemorrhagic Fever Arenaviruses

Abstract: Viral hemorrhagic fevers caused by the arenaviruses Lassa virus in Africa and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
101
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 40 publications
1
101
1
1
Order By: Relevance
“…F3406 differs chemically from several distinct classes of compounds that have been previously shown to inhibit arenavirus GPC-mediated membrane fusion by binding to a common site on GPC and stabilizing the prefusion GPC complex (39,(42)(43)(44)(45). Interestingly, previous work by Larson et al showed that arenavirus sensitivity or resistance to the cell entry inhibitor ST-193 correlated with the presence of V or M residues, respectively, at a GP2 position corresponding to M437 in LCMV (43).…”
Section: Discussionmentioning
confidence: 99%
“…F3406 differs chemically from several distinct classes of compounds that have been previously shown to inhibit arenavirus GPC-mediated membrane fusion by binding to a common site on GPC and stabilizing the prefusion GPC complex (39,(42)(43)(44)(45). Interestingly, previous work by Larson et al showed that arenavirus sensitivity or resistance to the cell entry inhibitor ST-193 correlated with the presence of V or M residues, respectively, at a GP2 position corresponding to M437 in LCMV (43).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we and others have identified novel classes of arenavirus entry inhibitors, including DNA aptamers (19) and several potent small-molecule inhibitors (3,20). While such entry inhibitors are likely efficacious early in infection, they are rather ineffective once the host cell has become infected.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to develop novel effective antiarenaviral drugs and vaccines, tasks that would be facilitated by a detailed understanding of the arenavirus molecular and cell biology. Recent studies have identified small molecule inhibitors of Tacaribe virus (7) and LASV (8) cell entry, but their antiviral activity in animal models of HF arenaviruses has not been examined.…”
mentioning
confidence: 99%